Empirical investigation of stock index futures market efficiency: The case of the Athens Derivatives Exchange - Andreou, Panayiotis; Pierides, Yiannos A. (My University, 2008)
Pricing and trading practices in the Athens Derivatives Exchange, a newly established derivatives market, result in significant futures arbitrage profit opportunities for low-cost traders. We find that a large part of the mispricing is due to transaction costs, but additional factors, such as anticipated volatility and time to maturity, also contribute. Ex ante tests reveal significant arbitrage opportunities that could have been exploited up to 30min after they had been identified. All different tests employed indicate that the derivatives market was inefficient during its early trading history because arbitrage opportunities persisted even after other market impact costs were taken into consideration.
Keywords: Cost of carry model; Market efficiency; Market frictions